PENERAPAN GOOGLE MAPS API PADA SISTEM INFORMASI GEOGRAFIS (SIG) TEMPAT WISATA DAN REKREASI KOTA PALANGKARAYA BERBASIS WEB - Pranatawijaya, Viktor Handrianus (Universitas Palangka Raya, 2014)
A new breakthrough on how to disseminate the potential of tourism and recreation is bydoing development of Geographic Information Systems ( GIS ) and recreational attractionsPalangkaraya city by using the web-based Google Maps API is intended for information on traveland recreation in the city of Palangkaraya into more forms and interactive and can be widelyknown to the public so it can be used as a promotional tool Palangkaraya city tourism .Development clump science informatics techniques in the field of software engineering,information systems, multimedia, and web programming can be realized with the development ofthe web-based GI .The study design is made consists of three stages: ( 1 ) data collection and analysis is doneby means of literature study and observation , ( 2 ) applying the waterfall method which has beenmodified with the stages are systems analysis to determine access rights along facilities , UML andERD are made, the design of the system by doing database design, navigation structure, interface,and integration of GIS data, the implementation of the system is done with pemrograma languagePHP, the database used is MySQL, and its GIS with Google Maps API, and testing systems usedblack box testing, and ( 3 ) the results of research in which a web -based GIS that was made into aready-made software .Created a web -based GIS in general have two users are administrators to manageinformation and visitors to view and search for information. The information referred to here is themap, text, and images.